Gender Innovation Lab Two Heads are Better Than One : Agricultural Production and Investment in Côte d’Ivoire - Donald, Aletheia; Goldstein, Markus; Rouane, Léa (World Bank, Washington, DC, 2022)
Increasing agricultural productivity and investment is critical to reducing poverty, particularly in Sub-Saharan Africa, where agriculture remains the dominant income-generating activity. One potential way to promote investment and improve the efficiency of household farm production is to empower women as co-managers and facilitate the coordination of production decisions within the family. The authors test this approach in Côte d’Ivoire through a couples training delivered to rubber producers, and find that including women in economic planning improved the efficiency of household farm production and promoted higher levels of investment.